Seismic performance and failure modes of the Jin'anqiao concrete gravity dam based on incremental dynamic analysis. (June 2019) - Chen, Deng-Hong; Yang, Zi-Hui; Wang, Min; Xie, Jing-Hui
Abstract: To investigate the potential failure modes of concrete gravity dams under seismic loads, a typical non-overflow dam section of the Jin'anqiao roller compacted concrete (RCC) gravity dam is taken as a case study. A compressive and integral analysis model of the dam body–foundation–reservoir water interaction system is established, in which the viscous–spring boundary and its corresponding free field input mechanism is employed to account for the dam–foundation interaction and fluid–solid coupling method is used to account for the dam–reservoir interaction. Based on the incremental dynamic analysis (IDA) method, IDA curves are generated with the relative displacement angle on the x -axis (damage measure, DM) and peak ground acceleration (PGA) on the y -axis (intensity measure, IM). The damage processes and potential failure modes for the Jin'anqiao gravity dam under different peak accelerations are investigated. It is concluded that under ground motion loadings of the Jin'anqiao dam, the locations at which functional failure may occur are mostly found in the stress concentration of the dam slope, the boundary of the rolling section, the junction between the dam and dam foundation, and the top of the corridor. Therefore, strengthening the seismic protection in these areas is conducive to improving the overall aseismic level of the dam. Highlights: Acompressive and integral analysis model of thegravitydam–foundation–reservoir water interaction system is established. Seismic performance of theJin'anqiao RCCgravity damis evaluated by using the incremental dynamic analysis(IDA). Damage processes of the Jin'anqiao RCCgravity dam under different peak accelerationsare investigated. Potential failure modes of the Jin'anqiao RCCgravity dam under extreme loadsare revealed.